UiTM, Malaysia and Abubakar Tafawa Balewa University, Nigeria strengthen global ties with Memorandum of Understanding / Noorsuhada Md Nor and Abdullahi Nafiu Zadawa - Md Nor, Noorsuhada; Zadawa, Abdullahi Nafiu (UiTM Global @ Office of International Affairs, 2024)
Penang, June 24, 2024 – Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia, has further solidified its international presence by signing a Memorandum of Understanding (MoU) with Abubakar Tafawa Balewa University (ATBU) Bauchi, Nigeria. This pivotal agreement, formalised during a virtual ceremony, aims to enhance collaboration in research, publications, institutional exchanges, and the development of teaching and learning between the two universities.